Pillar of the Mandapa of Sitaleshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The columns in the mandapa (pillared hall) of the Sitaleshwar Temple, a subsequent addition, feature various figures, including women, Shaiva ascetics, and dikapalas (gods of cardinal directions). The Shaiva ascetics are depicted, occasionally adorned with a substantial jatabhara (braided hairdo), sporting mustaches and long beards. They are presented with bare upper bodies, while the lower body is covered with a langot (a type of underclothes or loincloth).